Modelo de maturidade para processos certificados em sistemas agroindustriais - Geraldo Magela Jardim Barra (2015)
This thesis aims to develop and validate a maturity model for certified processes in agroindustrial systems so that the relationship between maturity of the firms certified processes and their impact on the marketing and financial performance could be evaluated. We started with the premise that the process certification favors the firm to go evolutionary processes influencing performance gains, since certification is spreading tool and institutionalizing best production practices. The hypothesis of this study is that the level of maturity of the certificates processes of the companies surveyed are positive and strongly linked to the performance of these organizations. It is believed that this issue is relevant to the coffee sector, especially in this time the coffee market has created opportunities for differentiation. This is a descriptive and conclusive study and is divided into two stages: qualitative with three groups of experts (specialists in processes, coffee experts and members of the FCC - Federação de Cafeicultores do Cerrado) and quantitative with growers that have been certified UTZ . For this, we developed a maturity model based on the UTZ certification called MMSAG (Maturity Model for Process Certificates in Agroindustrial System). After extensive research on process maturity and certification in coffee production, the maturity model was developed. This model was built based on the code of conduct UTZ Certified (2015a), and then validated by experts from business and academic branches through interviews and the focus group method. After validation by experts, the questionnaire MMSAG was applied to farmers certified by UTZ through a survey. The survey data were obtained through structured questionnaires, which were sent by regular mail and electronic mail to respondents. The research included a universe of 203 producers, resulting in the collection of data 55 respondents. Data from the survey were analyzed using descriptive statistics, correlation analysis and linear regression analysis. The survey results showed that companies with higher certificates processes maturity level tend to perform better in critical areas of the financial performance and market. The results indicate that, in addition, companies with the highest certification times showed the highest levels of maturity. It was noticed that higher levels of process maturity are established through an evolutionary process of dissemination of best practices and certification of fruit are related to performance of certified firms. In addition, it is necessary to highlight the role of UTZ certification in improving the management of processes. The major contribution of this thesis for agribusiness and for studies in the area of process management is focused on the proposed maturity model, which allows to identify the critical points of each firm individually, making it possible to highlight the points of improvement of processes of certified firms. Moreover, the MMSAG enables the development of collective strategies, it is possible to check common points of improvement in strategic groups to guide collective efforts for better performance results. The proposed maturity model will be able to categorize farmers groups according to the levels of process maturity and performance with regard to the requirements of certifications.